2006
DOI: 10.1111/j.1365-3148.2006.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting loss and gain of red cell volume in cardiac surgery patients

Abstract: Haemoglobin may be a poor indicator of changes in red cell volume (RCV) because of factors such as haemodilution. This study has been designed to analyse what peri-operative variables may be associated with loss or gain in RCV due to bleeding or transfusion. Prospective observational study. Single centre study based in a regional cardiac surgery centre. Twenty-nine elective adult cardiac surgery patients. Loss and gain of RCV were measured in theatre and for the first 24 h post-operatively. Patient and operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This enormous range may be attributed partially to a subjectively based instead of an evidence‐based practice and may indicate unnecessary transfusion. Variation in perioperative transfusion practice patterns, however, may also be influenced by differences in patient population among the study centers, including comorbidities as well as other patient‐related factors such as age, body size, 7 or preoperative anemia 10,23,24 . Moreover, preoperative medication with anti‐PLT agents and anticoagulants as well as preoperative transfusion of blood products may impact intra‐ and postoperative transfusion needs 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…This enormous range may be attributed partially to a subjectively based instead of an evidence‐based practice and may indicate unnecessary transfusion. Variation in perioperative transfusion practice patterns, however, may also be influenced by differences in patient population among the study centers, including comorbidities as well as other patient‐related factors such as age, body size, 7 or preoperative anemia 10,23,24 . Moreover, preoperative medication with anti‐PLT agents and anticoagulants as well as preoperative transfusion of blood products may impact intra‐ and postoperative transfusion needs 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that the ability of an individual to tolerate RCV loss is dictated by the preoperative RCV [5]. As gender and weight are major determinates of RCV, we divided preoperative RCV data into male and female categories with three weight‐based subdivisions [4].…”
Section: Methodsmentioning
confidence: 99%
“…There is currently no convenient and repeatable method for determining RCV. This has led us to develop a transfusion protocol that involved a transfusion threshold derived from body weight (as an estimate of preoperative RCV and therefore the ability to tolerate RCV loss [5]), and a dilution factor to allow the adjustment of postoperative Hb (Table 1). We report preliminary findings of using this ‘RCV transfusion threshold’ as a guideline for the use of RBCs in patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The most robust formula to date for the calculation of RCV has been provided by the International Council for Standardization in Hematology [10]. Results from previous research have indicated that weight and gender are the most important components of this formula in determining RCV [7]. As such, data from a previous study were divided into male and female categories with three further weight based subdivisions [4].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, at the time of writing, such a technique does not exist. This has led us to develop a RCV‐based transfusion guideline incorporating both body weight (as a guide to the ability to tolerate RCV loss) and a dilution factor in order to give greater relevance to postoperative Hb (Table 1) [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%